A review on the gap and opportunities in forest biomass studies in Sarawak, Malaysia - Kueh, Roland Jui Heng; Demies, Malcom; Waseem Razzaq Khan, .; Latiff, A. (Jabatan Perhutanan Semenanjung Malaysia, 2023)
The forest ecosystem is a significant carbon reservoir. The carbon estimation can be determined using biomass data. Forest biomass is estimated using a biomass equation model or by felling trees. The introduction of Reducing Emissions from Deforestation and Forest Degradation plus (REDD+) has increased the need for accurate techniques to estimate forest biomass as readiness to participate in carbon markets requires methods acceptable to both buying and selling countries. The objectives of this review were to undertake a historical assessment of forest biomass studies that had been conducted, current localised equation models, and to discuss areas concerning biomass studies in Sarawak, Malaysia. The current study found 36 publications on biomass studies in Sarawak. When compared to other forest types, Mixed Dipterocarp Forest has higher above ground biomass (AGB), while logged-over secondary forest has more AGB than shifting cultivated secondary forest. There have been numerous reports of wide variations in biomass storage as below ground biomass (BGB), litter, and soil organic matter (SOM). For above ground forest biomass, 13 equations were created while two equations were developed for below ground forest biomass. Combinations of forest inventory data with biomass regression models are among the most popular strategies used in this review to determine forest biomass in Sarawak. Remote sensing tool still has room for improvement in forest biomass estimation and model development in Sarawak. Information gaps in numerous aspects of forest biomass provide opportunities for study to improve the current forest biomass database information.